Histological Characteristics and Early-Stage Diagnosis Are Associated With Better Survival in Young Patients With Epithelial Ovarian Cancer: A Retrospective Analysis Based on Surveillance Epidemiology and End Results Database - Huang, Yue; Ming, Xiu; Li, Bingjie; Li, Zhengyu (Frontiers in Oncology, 2020)
Purpose： To analyze the potential prognostic factors of epithelial ovarian cancer (EOC) in women aged under 35 compared to those aged 60-79. Methods： Cases were retrospectively obtained from SEER database. Clinical characteristics, such as race, histological type, AJCC stage, laterality of tumors, CA125 results, and surgical strategies, were analyzed in < 35 years group and 60-79 years group. Kaplan-Meier survival curves were used to evaluate overall survival (OS) and cause-specific survival (CSS). Cox proportional hazard model was used to identify the predictors for CSS. Results： 16,847 EOC patients diagnosed in 2004-2015 were identified from SEER database, with 1,015 aged under 35 and 15,833 aged 60-79. In < 35 years group, mucinous (32.2%) was the most common histological type, followed by high-grade serous (26.6%) and endometrioid (18.3%), while in 60-79 years group, high-grade serous (68.3%) represented the leading histological type. Most young women were diagnosed at stage Ⅰ (57.7%), while most old women were diagnosed at stage (48.1%). Both 5-year OS and 5-year CSS were higher in < 35 years group (5-year OS: 76.00% vs 40.18%, p < 0.001; 5-year CSS: 83.56% vs 55.18%, p < 0.001). The multivariate analysis identified histological type and stage as prognostic factors for CSS in both groups. Endometrioid represented a positive predictor for CSS, while carcinosarcoma and malignant Brenner were related to a worse CSS. (< 35 years group: carcinosarcoma vs endometrioid: HR 5.630, p=0.024; malignant Brenner vs endometrioid: HR 4.005, p < 0.001; 60-79 years group: carcinosarcoma vs endometrioid: HR 3.606, p < 0.001; malignant Brenner vs endometrioid: HR 2.291, p < 0.001). Tumors laterality, CA125 levels, surgery and lymphadenectomy failed to be associated with the CSS in < 35 years group, while found to be independent risk factors in 60-79 years group. Conclusion： EOC women aged under 35 had a better survival outcome over EOC women aged 60-79, owing to high proportion of endometrioid and mucinous types in histology, as well as early-stage diagnosis. Identification of histological types and gene profiles should be underscored in young EOC patients.